Influence of biogass slurry and urea on yield and quality of okra (Abelmoschus esculentus L.) fruits - Ghimire, K; Gautam, DM; Mishra, K; Pande, KR; GC, A (Journal of Agriculture and Environment, 2015)
The study was conducted on sandy loam soil at IAAS Rampur, Chitwan during May to September, 2012 to evaluate the effect of different combinations of biogas slurry and urea on production of okra, laid out in a two-factor RCBD with three replications. Altogether ten treatments consist of two varieties namely Arka Anamika - open pollinated and Jaikisan-62-F1 hybrid and four different levels of biogas slurry and urea combination (urea75%+biogas slurry25%, urea50%+biogas slurry50%, urea25%+biogas slurry75% and biogas slurry100%) and only inorganic chemical (75:60:50 kg NPK/ha) as control. All treatments were based on fulfillment of required nitrogen for the crop. The results showed that application of urea50%+biogas slurry50% increased plant height, leaf area, number of leaves and number of nodes at final harvesting. Treatment urea50% + biogas slurry50% allow maximum number of pickings/plant (23.2) and number of fruits/plant (23.5) resulting highest yield/plant (376.3 g). Among the varieties, Jaikisan-62 is superior in terms of growth, yield and post harvest character than Arka Anamika. The net return (Rs. 474,136/ha) and mean B/C ratio was highest (2.59) in Jaikisan-62 treated with urea50%+biogas slurry50%. So, for the commercial production hybrid variety is suggested.